Potential Analysis and Development of Educational Tourism Objects for Citaman Indah Coffee Plantation, Cijeruk Village - Ami, Ashari; Aan, Andriana; Mochamad, Wildan Alimufti; Ahmad, Sidiq; Annisa Icha, Nurul; Lestari, Asti Tri (AbdimasMu UMTAS, 2023)
The potential of coffee plantations to become an educational tourism object is very high. This community service was carried out in Cijeruk Village, Dayeuh Luhur District, Cilacap Regency, Central Java Province. Cijeruk Village is located in the westernmost part of Cilacap Regency and Central Java which is directly adjacent to West Java Province. Its territory is in a mountain valley which is a series of three corner mountains. The altitude of the Cijeruk village area is between 200-1,200 m above sea level with several mountain peaks such as Mount Subang (1,206m), Mount Karang Gumantung (1,185m), Mount Palasari (1,062m) and others. Cijeruk Village is one of the villages that has high natural tourism potential, but has not developed into a mainstay tourist village. The objectives of this service are (1) to identify the potential of the Citaman Indah coffee garden educational tourism object, (2) to identify the problems that become obstacles in the development of the coffee plantation educational tourism object, and (3) to determine the priority scale for the development of the Citaman coffee garden educational tourism object. Beautiful. The results obtained (1) The potential of the Citaman Indah coffee plantation educational tourism object is quite high, but the tourism object has not been managed. (2) The obstacles faced are quite diverse, starting from internal factors: wild animals such as wild boars are still abundant, land boundaries with Perhutani land, some lands are still managed by individuals. Constraints from external factors: the long distance from the sub-district city center, road access can only be passed by dirt bikes and walking, accessibility infrastructure has not been developed, there are no development and promotion activities. (3) create photo spots to introduce and promote the beautiful Citaman coffee garden educational tourism object.